Marine radioactivity database 2003-2018 - Osores, José (2018)
As part of the IAEA project K41017 "Behavior and Effects of Natural and Anthropogenic Radionuclides in the Marine Environment and their use as Tracers for Oceanography Studies", radioactivity data on sediments and marine biota collected in the Grau Sea of the Pacific Ocean region, which extends along the Peruvian coast in an area of 3080 km and a width of 200 miles offshore are presented. The analyzes corresponding to the 2003-2018 period were carried out by the Radioecology Laboratory of the Peruvian Institute of Nuclear Energy (IPEN) by means of high resolution gamma spectroscopy (Ra-226, Pb-210, Cs-137 and K-40) and by alpha spectroscopy (Po-210).